FEVER AND CONFUSION IN A RETURNING SOLDIER. Issue 11 (9th October 2013) - Chandratheva, Arvind; Singh, Anil Ramlackhan; Sturman, Steve; Chaganti, Sridhar; Jacob, Saiju
Abstract : A 36–year–old army engineer returned from a 6–week deployment in Afghanistan. He had complained of upper respiratory tract infection even before his travel. On return he was found to be increasingly sleepy and later developed unsteadiness, slurred speech and confusion. His initial blood tests were normal, with CSF and MRI suggesting signs of encephalitis. He continued to deteriorate, requiring intubation and ventilation. Several bacterial, viral, protozoal and fungal tests were negative. He developed pancytopenia requiring frequent packed red cell and platelet transfusions. Spleen was found to be marginally enlarged. A bone marrow examination showed hyperplastic left shift pattern with marked granulocyte, red cell and megakaryocyte precursor activity. At this stage his EBV DNA was found to be strongly positive, with over a million copies identified in the blood. EBV was also isolated from the CSF. His pancytopenia continued to worsen, with worsening neuroinflammation on MR imaging. The ferritin level was very high at 14000 mcg/L, with low fibrinogen and raised soluble CD25. A diagnosis of haemophagocytic lymphohistiocystosis (HLH) was made as per established criteria. He was treated with multiple chemotherapeutic agents including Etoposide, Cyclosporine, Rituximab and Dexamethasone initially. After an initial good response, the HLH relapsed, and second line therapy including Alemtuzumab (Campath) and intrathecal methotrexate was added with a view of definitive treatment, which is allogenic bone marrow transplantation. Haemophagocytic lymphohistiocytosis is a rare and life–threatening immune dysregulation syndrome predominantly affecting infants and children. HLH typically presents with prolonged febrile illness, pancytopenia, organomegaly and neurological symptoms. Perforin–dependent lymphocytic cytotoxic function seems to be impaired in the majority of patients, although perforin levels and other genetic susceptibility markers (Eg: XLP1, XLP2, ITK) were normal in this patient, suggesting an immune trigger. Secondary HLH occurs in response to infections, malignancy or autoimmune diseases. The common infectious agents known to cause HLH includes EBV, CMV, HHV8, HIV, Mycobacteria, mycoplasma, leishmania, plasmodium and Cryptococcus. Neoplastic triggers include leukemias and lymphomas, particularly T–cell lymphoma. Exact pathophysiology of secondary HLH is less well understood than in the genetic subtypes. Neurological symptoms including altered consciousness, seizures, meningism and ataxia may be seen in approximately 30% of patients and carries a poorer prognosis. Laboratory findings supporting the diagnosis in addition to the pancytopenia are very high ferritin levels (more than 10000 mcg/L), hypofibrinogenemia, hypertriglyceridemia, elevated liver enzymes, low albumin, elevated soluble CD25 levels and reduced NK cell cytotoxicity. Treatment is aimed at suppressing the hyperinflammatory component of the condition, using steroids, cyclosporine, etoposide, intrathecal methotrexate and alemtuzumab. EBV–triggered HLH often require concomitant Rituximab therapy. Once remission is achieved, haematopoietic stem cell transplantation is recommended. Despite the advances in therapy unfortunately HLH is fatal in 40–60% of patients. Neurologists should be aware of rare, but potentially treatable haematological conditions which can manifest with pure neurological symptoms. HLH is almost invariably a fatal disease if not diagnosed and treated early.